Achieving Corporate Sustainability Using Smart Technologies with a Focus on Safety Management - Rangasamy, Elangovan (Digital Repository of Theses, 2025)
In the bottom-line corporate landscape, achieving sustainability with safety manage-ment is no longer an option but a necessity driven by regulatory demands, stakeholder expec-tations, and the imperative to mitigate environmental impacts. This research explores the piv-otal role of smart technologies in advancing corporate sustainability, with a specific focus on enhancing safety management practices. Smart technologies, encompassing the Internet of Things (IoT), Artificial Intelligence (AI), and big data analytics, offer unprecedented capabil-ities to monitor, analyse, and optimize various operational facets of businesses. This study delves into how these technologies can be strategically currently deployed to foster a sustain-able corporate environment, ensuring not only environmental stewardship but also the safety and well-being of employees. The research adopts a mixed-methods approach, combining quantitative data analysis with qualitative case studies to provide a comprehensive understanding of the impact of smart technologies on sustainability and safety management. Key areas of investigation include the implementation of IoT-enabled safety devices, AI-driven predictive maintenance systems, and big data analytics for real-time risk assessment and mitigation. The findings reveal that smart technologies significantly enhance the efficiency and effectiveness of safety manage-ment systems, leading to reduced incident rates, improved compliance with safety regula-tions, and enhanced overall sustainability performance. Moreover, this research underscores the importance of an integrated approach to cor-porate sustainability, where technological advancements are aligned with organizational poli-cies and cultural shifts towards a safety-first mindset. The implications of this research extend to policymakers, industry leaders, and safety professionals, providing actionable insights and strategic frameworks to leverage smart technologies for sustainable and safe corporate opera-tions.